Enhancing cubosome functionality by coating with a single layer of poly-epsilon-lysine - Deshpande, Sonal; Venugopal, Edakkal; Ramagiri, Shobha; Bellare, Jayesh R.; Kumaraswamy, Guruswamy; Singh, Neetu (ACS Applied Materials & Interfaces, 2014)
We report the preparation and characterization of monoolein cubosomes that can be easily surface modified through adsorption of a single layer of cationic poly-epsilon-lysine. Poly-epsilon-lysine coated cubosomes show remarkable stability in serum solution, are nontoxic and, are readily internalized by HeLa cells. The poly-epsilon-lysine coating provides chemical handles for further bioconjugation of the cubosome surface. We also demonstrate that the initial release rate of a hydrophilic drug, Naproxen sodium, from the cubosomes is retarded with just a single layer of polymer. Interestingly, cubosomes loaded with Naproxen sodium, recently shown to have anticancer properties, cause more apoptosis in HeLa cells when compared to free unencapsulated drug.
Keywords: bioconjugation; cubosomes; drug delivery vehicle; dual loading; theranostics